Redefining Ternstroemia venosa (pentaphylacaceae s.l.): morphometric and taxonomic analyses of the T. brasiliensis complex reveal new synonymizations and a new species from the Brazilian Atlantic Rainforest - Vieira, Jaqueline Alves [UNESP]; Jordão, Valner Matheus Milanezi; Rezende, Wadson Rodrigues; van den Berg, Cássio; Sampaio, Daniela [UNESP] (Botanical Journal of the Linnean Society, 2025)
Ternstroemia venosa was described in 1821, seven years before Ternstroemia brasiliensis, a synonym. However, the type material of T. venosa was poorly known and the name has been treated as dubious for many years. Therefore, the name T. brasiliensis has been used for the most widespread species of Ternstroemia in Brazil. Over the past 200 years, six names have been circumscribed within T. brasiliensis, and the species was also divided into two. Here, we report the rediscovery of the lost material of T. venosa, a nomenclatural treatment, as well as morphometric and bioclimate data analyses, which support the synonymization of all these names under the T. venosa. A nomenclatural review was carried out to support the PCA and Ward’s Cluster analysis of nine vegetative and 25 reproductive characters from a total of 259 specimens as well as eco-geographic features of 215 specimens. Furthermore, our results reveal another morphologically well-delimited entity with distinct geographic ranges. Based on these discoveries, we change the status of T. brevipes var. blanchetii and recognize at species level, T. blanchetii (Choisy) J.A.Vieira & D. Sampaio.
Redefining Ternstroemia venosa (pentaphylacaceae s.l.): morphometric and taxonomic analyses of the T. brasiliensis complex reveal new synonymizations and a new species from the Brazilian Atlantic Rainforest
Keywords: Ericales s.l.; Taxa, floral traits; Morphology, geographical variation; Phytogeography, leaf surface morphology; Morphology, morphological variation; Morphology, Ternstroemiaceae; Taxa